Molecular crop protection using recombinant DNA techniques - Keese, P.; Pinto, Y. (2003)
Biotechnology is the name that has been given to a very wide range of agricultural, industrial, and medical technologies that make use of living organisms or parts of organisms to provide new products and services. Although the term refers to much broader technology than genetic engineering, the techniques of genetic engineering are of such importance that the two terms have become virtually synonymous. This report on molecular crop protection is by no means exhaustive as there is much work in the private and public sectors which is not reported or published. Much preparatory work has been done to allow the basic adaptation and application of this technology to crops and crop systems. However, the emphasis is on approaches that have been used in crop plants and aims to reflect the scope of current work and, more importantly, the future potential of biotechnological tools for improving crops which are of specific importance to Africa.